Cooperative Strategies in the Lens of Filipino Teacher Educators: An Appreciative Inquiry Study - Madaliday, Sandra (International Journal of Arts, Sciences and Education, 2025)
In the ever-evolving field of education, employing effective teaching strategies is crucial for enhancing student skills, particularly in the Filipino language. This study utilized the Appreciative Inquiry methodology to examine the cooperative strategies employed by veteran Filipino teachers and how they contribute to improved learning outcomes. The research involved eight participants, all Filipino language specialists from Sultan Kudarat State University with at least three years of teaching experience, selected through purposive sampling. Thematic analysis was employed to analyze the data. The study found that cooperative strategies fostered greater student engagement, deeper understanding of the subject matter, and improved communication skills. However, teachers encountered challenges such as time management and uneven student participation. To address these, they implemented clear role assignments, provided guidance, and utilized conflict resolution techniques. Based on the analysis, the use of cooperative teaching methods in Filipino instruction significantly contributed to increased student participation and engagement. Overall, this study confirmed the effectiveness of cooperative strategies in fostering collaboration, trust, and positive relationships within the classroom.